USE OF CANNABINOIDS IN THE TREATMENT OF INFLAMMATORY BOWEL DISEASE: A REVIEW OF CLINICAL AND INTERVENTION STUDIES - Anita Janda; Magdalena Rosiewicz; Marcin Durowicz; Iwona Górnicka; Aleksandra Pastuszek; Karolina Bieńkowska; Jan Drzymała; Urszula Kierepka; Sylwia Bartolik (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Inflammatory bowel disease (IBD) is a general term used to describe a group of chronic inflammatory diseases of the gastrointestinal tract with complex etiologies. They mainly include Crohn's disease (CD) and ulcerative colitis (UC) .Purpose of the work: The purpose of this paper is to present current knowledge on the use of cannabinoids in the treatment of inflammatory bowel disease, with a particular focus on their impact on patient well being.Material and methods: The study is based on a review of the scientific literature, including clinical and experimental studies on the effects of cannabinoids on the gastrointestinal tract and their use in the treatment of IBD.Results: The endocannabinoid system (ECS) plays an important role in modulating many physiological processes, including maintenance of intestinal homeostasis, regulation of intestinal function, visceral sensation, modulation of gastrointestinal motility and immunomodulation of inflammation in IBD. Studies have shown that their use leads to a reduction in abdominal pain, emotional distress, stool frequency and anorexia nervosa. They also found higher rates of depression, smoking and alcohol consumption among IBD patients who used cannabis. The long-term safety profile of cannabinoids in IBD patients has not been established.Summary: Cannabinoids have the potential to be effective supportive therapies for inflammatory bowel disease, but more research is needed to determine their long-term safety and optimal dosage.